2020
DOI: 10.3389/fimmu.2020.01959
|View full text |Cite
|
Sign up to set email alerts
|

Combating COVID-19: MVA Vector Vaccines Applied to the Respiratory Tract as Promising Approach Toward Protective Immunity in the Lung

Abstract: The lung is the vital target organ of coronavirus disease 2019 (COVID-19) caused by infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). In the majority of patients the most active virus replication seems to be found in the upper respiratory tract, severe cases however suffer from SARS-like disease associated with virus replication in lung tissues. Due to the current lack of suitable anti-viral drugs the induction of protective immunity such as neutralizing antibodies in the lung is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…The absence of detectable anti-S IgA in serum was in accord with the result of Hassan et al ( 13 ), who found IgA after IN but not IM vaccination with an adenovirus CoV-2 S vaccine. MVA can be administered orally, IN, and by aerosol, and the IN route has been shown to stimulate bronchus-associated lymphoid tissue and serum IgA ( 57 59 ). Even though IM administration of the rMVA CoV-2 S vaccines greatly reduced and rapidly eliminated virus replication in the nasal turbinates, IN administration might have a greater ability to reduce CoV-2 spread.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of detectable anti-S IgA in serum was in accord with the result of Hassan et al ( 13 ), who found IgA after IN but not IM vaccination with an adenovirus CoV-2 S vaccine. MVA can be administered orally, IN, and by aerosol, and the IN route has been shown to stimulate bronchus-associated lymphoid tissue and serum IgA ( 57 59 ). Even though IM administration of the rMVA CoV-2 S vaccines greatly reduced and rapidly eliminated virus replication in the nasal turbinates, IN administration might have a greater ability to reduce CoV-2 spread.…”
Section: Discussionmentioning
confidence: 99%
“…Poxviruses and particularly modified vaccinia virus Ankara (MVA) strain have previously demonstrated to provide protective immunity against influenza virus H5N1 in mice [ 11 ]. The MVA vaccinia virus strain has also been considered as a promising candidate for vaccine development against coronaviruses, due to their potential targeting of mucosal surfaces of the respiratory tract [ 57 ]. A synthetic MVA-based vaccine platform has been engineered by application of a unique three-plasmid system for co-expression of SARS-CoV-2 S and nucleocapsid proteins [ 46 ].…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…Another point to consider is the route of administration, which can affect the ability of vaccines to prevent spread. In addition to IM and subcutaneous routes, rMVAs can be administered orally, IN and by aerosol(53)(54)(55)(56)(57)(58)(59)(60). Although IM administration of the rMVA CoV-2 S vectors greatly reduced and rapidly eliminated virus replication in the nasal turbinates, it will be of interest to determine whether IN administration would prevent replication entirely.Materials and MethodsCells.…”
mentioning
confidence: 99%